Perancangan E-library BNI Corporate University - Teddy Gunnar Solkjaer (Journal of Information and Technology, 2022)
The rapid development of websites both in terms of users and supporting technology has encouraged the emergence of many website creation service providers, one of which is BNI. Digital Library is the application of information technology as a means to store, obtain, and disseminate scientific information in digital format. Or in a simple analogy as a place to store library collections that are already in digital form.